Jump events in a 3D Edwards-Anderson spin glass - Mártin, Daniel Alejandro (2017)
The statistical properties of infrequent particle displacements, greater than a certain distance, are known as jump dynamics in the context of structural glass formers. We generalize the concept of a jump to the case of a spin glass, by dividing the system into small boxes, and considering the infrequent cooperative spin flips in each box. Jumps defined this way share similarities with jumps in structural glasses. We perform numerical simulations for the 3D Edwards-Anderson model, and study how the properties of these jumps depend on the waiting time after a quench. Similar to the results for structural glasses, we find that while jump frequency depends strongly on time, the jump duration and jump length are roughly stationary. At odds with some results reported on studies of structural glass formers, at long enough times, the rest time between jumps varies as the inverse of jump frequency. We give a possible explanation for this discrepancy. We also find that our results are qualitatively reproduced by a fully-connected trap model.